Uma análise do Plano de Gestão de Resíduos Sólidos do município de Varginha - Borges, Stella Maria Sulz Barbosa (2018)
Guided by Law no. 12.305 of August 2nd, 2010, which instituted the National Solid Waste Policy (PNRS), which makes the Union, states, municipalities and the society responsible for adapting to the regulatory precepts of the theme, this work presented, as general objective, the analysis of the Municipal Plan Management of Solid Waste (PMGIRS) of the southern Minas Gerais municipality, Varginha, according to the guidelines established by art. 19 of the PNRS. As specific objectives, the comparative study between Varginha PMGIRS and the minimum content of article 19 of the PNRS through the script for Integrated Management Plan for Solid Residues Elaboration (PGIRS) from the Ministry of the Environment (MAM), Goals Plan indicated by the Plan and developed by the municipality and, in the end, the contributory suggestion for the appropriate destination of the residues with the creation of an interactive map, in a website, bringing specific information about the disposal sites, listed by the municipality (PMV). Although the research general aim is limited to the local scope, this work's organization adopted global parameters which guidelines started to be form in the 1970s through the perception that the survival of all species would be conditioned to the preservation of the planet's natural resources. During this period, the approach to environmental issues has undergone a positive and notorious transformation through the debates promoted by the conferences and other international events since then, grounding the current public environmental policies. Accordingly with these new policies, Varginha has been empirically improving, with advances, its solid waste management model. The elaborated plan, in addition to being devoid of methodology, brought superficial approaches to the article 19's clauses of the PNRS. Regarding the propositions and the goals plan, a considerable part was not implemented. In conclusion, an interactive map was suggested in order to make the possibilities of recycling offered by the municipality to the residents known. In order to do so, the qualitative approach was adopted, based on the exploratory and descriptive research, which data were collected secondary with the organs that compose the municipality's direct administration.